Digitization and Integration of Immigration Data: Citizenship and Mix-Marriage Status Questioning the "Citizenship" Policy in Indonesia - Wilonotomo; Rofii, Muhammad Syaroni; Nugroho, Tri Sapto Wahyudi Agung; Jazuli, Ahmad; Lagustiani, Sri Humana (Journal of Cultural Analysis and Social Change, 2026)
This research addressed the legal status of Indonesian citizenship and mixed marriages. Migration drives indigenous-foreign marriages. Foreign partners of native citizens have higher prospects of getting citizenship, residency, and employment in their new countries, which dramatically impacts mixed marriages. Government must recognize, defend, safeguard, facilitate, and realize. The Indonesian Constitution defines citizenship as socio-political membership and a human right. It examined "citizenship" and the state's involvement in it. It emphasised the need to understand Indonesian citizenship and mixed marriage, specifically legal status. Citizenship services are offered by the Directorates General of Immigration and General Law Administration of the Ministry of Law. Directorate General of Immigration controls non-citizen data, while the General Law Administration handles citizenship petitions and determinations. It highlighted the Ministry of Law and the Ministry of Immigration and Correction services policy and data management. Citizenship offers individuals and the nation privileges and responsibilities. The empirical legal method compared legal requirements to Indonesian events. Field research analyzed legal systems, community responses to government, and social effects of existing legislation. Combining case studies and legal rules improves research. Data collection includes open interviews, visual aids, and targeted sampling. Division of citizenship services into AHU and Immigration Directorate General The two directorates-General process pure citizenship, mixed marriages, and restricted dual citizenship applications. Lawful citizens who choose foreigners or Indonesians cannot be reported by the AHU and Immigration authorities because to limited "data access".